Towards a Model for Managing Diversity and Inclusion in Software Development Teams - Miranda, Michele; Prikladnicki, Rafael (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
[Context] Information technology companies increasingly understand the importance of diversity and inclusion in software development teams. For this reason, they seek to implement diversity management models to enhance the positive effects of this inclusion. However, there is no single model for managing diversity, which makes it possible for each company to develop a model that works according to their expectations and demands. The literature about diversity management mentions that a large number of these models focus their efforts on managing distinct skills for team composition and on recruiting and selecting professionals with different profiles as a way of responding to the demand for more diversity in software development teams. [Objective] This work developed an initial model for managing diversity and inclusion in software development teams. Our goal is to explore how the practice of diversity management has occurred in this context. [Method] To achieve this goal, we developed an action research within a multinational organization in Brazil. [Results] We proposed a model for managing diversity characterized by three stages: Inclusion, Development, and Representation.[Conclusion] The main contribution of this paper is the model to help companies to manage diversity and inclusion and the discussion about the importance of thinking on diversity and inclusion in a structured way in the context of software development teams.